The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1038/s42255-019-0081-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic plasticity of HIV-specific CD8+ T cells is associated with enhanced antiviral potential and natural control of HIV-1 infection

Abstract: Nature MetabolisM T cells ex vivo can be isolated from HICs but not from cART individuals 8,10,18 (Fig. 1a). In the present study, it was first investigated whether this capacity of HIC CD8 + T cells could be found among naive, central memory, transitional memory and effector memory CD8 + T cell subsets (see Supplementary Fig. 1). As expected, naive CD8 + T cells from HICs had no HIV-suppressive capacity. In contrast, all sorted memory CD8 + T cell subsets from HICs, but not from cART individuals, suppressed H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
119
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(131 citation statements)
references
References 67 publications
12
119
0
Order By: Relevance
“…This was traduced in a dependency on glucose of HIV-specific CD8+ T-cells from non-controllers to react to HIV antigens, while HIV-specific CD8+ T-cells from controllers were characterized by metabolic plasticity and being able to exert their function even in conditions of glucose deprivation. Of note, these differences in the metabolic program of cells from controllers and non-controllers could also be recapitulated with SIV-specific CD8+ T-cells from SICs and VIR CyMs from the present study (Angin et al, 2019b), further corroborating the validity of our CyM model to study the development of the protective CD8+ T-cell responses characteristics of HIV/SIV controllers. The present results extend these observations and support a key role for long-lived memory responses in the control of SIV.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This was traduced in a dependency on glucose of HIV-specific CD8+ T-cells from non-controllers to react to HIV antigens, while HIV-specific CD8+ T-cells from controllers were characterized by metabolic plasticity and being able to exert their function even in conditions of glucose deprivation. Of note, these differences in the metabolic program of cells from controllers and non-controllers could also be recapitulated with SIV-specific CD8+ T-cells from SICs and VIR CyMs from the present study (Angin et al, 2019b), further corroborating the validity of our CyM model to study the development of the protective CD8+ T-cell responses characteristics of HIV/SIV controllers. The present results extend these observations and support a key role for long-lived memory responses in the control of SIV.…”
Section: Discussionsupporting
confidence: 86%
“…In a recent single cell study (Angin et al, 2019b), we also found differences in the program of HIV-specific CM CD8 + T-cells from HIV controllers and non-controllers on cART: whereas HIV-specific CM CD8 + T-cells from HIC upregulated the expression of effectors genes linked with mTORC2 activation and cell survival (including CD127), central memory cells from non-controllers had a skewed profile associated with mTORC1 activation (including T-bet) and glycolysis. This was traduced in a dependency on glucose of HIV-specific CD8+ T-cells from non-controllers to react to HIV antigens, while HIV-specific CD8+ T-cells from controllers were characterized by metabolic plasticity and being able to exert their function even in conditions of glucose deprivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of IL-15 to enhance ADCC and augment NK cell mediated killing of HIV-infected target cells ex vivo (Garrido et al, 2018) may prove vital in the development of a functional cure for HIV. Our findings together with a recent report of IL-15 mediated metabolic reprogramming improving the efficacy of HIV-specific CD8 T cells from non-controllers (Angin, 2019), highlight the complementary effects of such an approach to simultaneously re-invigorate multiple arms of the immune response.…”
Section: Discussionsupporting
confidence: 57%
“…Metabolic inflexibility has been recently described to underline dysfunctional HIV-specific CD8 T cells (Angin, 2019). In particular, the polyfunctionality of CD8 T cells from spontaneous HIV-1 controllers was more reliant on mitochondrial function rather than glycolysis and differences in glucose dependency described in SIV-specific CD8 T cells have been found to correlate with their capacity to supress SIV infection.…”
Section: Discussionmentioning
confidence: 99%